A Review on “Non-Violent Communication: A Language of Life” by Marshall B. Rosenberg - Azgın, Bilge (Journal of History Culture and Art Research, 2018)
This article aims to celebrate the life and the work of renowned peace activist Marshall B. Rosenberg who elucidated the principles and tools of his Non-Violent Communication (abbreviated as NVC) approach in his untimely book “Non-Violent Communication: A Language of Life.” Indeed, “Non-Violent Communication: A Language of Life" is the magnum opus of Rosenberg’s lifetime work and it stands out as a foundational transformative educational toolbox in developing the cognitive and emotive skills for compassion and reconciliation at both personal and societal level. Simply defined as “a way of communicating that leads us to give from the heart”, Rosenberg’s “Non-Violent Communication: A Language of Life” provides its readers with effective and accessible tools to remove the barriers that stand in front of compassionate communication.